2005
DOI: 10.1631/jzus.2005.b0991
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical studies on water hyacinth (Eichhornia crassipes(Mart.) Solms) under the influence of textile wastewater

Abstract: Mahmood et al. / J Zhejiang Univ SCI 2005 6B(10)Abstract: Water hyacinth (Eichhornia crassipes (Mart.) Solms) is a prolific free floating aquatic macrohpyte found in tropical and subtropical parts of the earth. The effects of pollutants from textile wastewater on the anatomy of the plant were studied. Water hyacinth exhibits hydrophytic adaptations which include reduced epidermis cells lacking cuticle in most cases, presence of large air spaces (7~50 µm), reduced vascular tissue and absorbing structures. Texti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 7 publications
8
56
1
6
Order By: Relevance
“…Similar findings had also been reported by Dipu et al, (2010), Yadav et al, (2011), Dhote (2007), Shah (2010), Mahmood et al, (2005).…”
Section: Results and Discussion Ph And Ecsupporting
confidence: 89%
“…Similar findings had also been reported by Dipu et al, (2010), Yadav et al, (2011), Dhote (2007), Shah (2010), Mahmood et al, (2005).…”
Section: Results and Discussion Ph And Ecsupporting
confidence: 89%
“…Mahmood et al (2005) reported that in the presence of textile industry effluents, E. crassipes plants exhibited a reduction in cell size in leaf tissues, whereas Pereira et al (2011) found no deleterious effects in anatomy of leaves and roots of this species in the presence of arsenic. In Plantago major, lead reduced stomatal density as well as stomatal conductance and vascular bundle size (Kosobrukhov et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Esses autores constataram ainda aumento na atividade da peroxidase e na peroxidação lipídica, decorrente do estresse oxidativo na presença de arsênio. As modificações anatômicas de E. crassipes sob estresse são ainda pouco relatadas; contudo, Mahmood et al (2005) verificaram diferenças no tamanho das células dos tecidos dessa espécie crescendo sob efluentes de indústria têxtil.…”
Section: Introductionunclassified